Faktor Risiko Yang Berpengaruh Terhadap Kejadian Hipertensi Pada Wanita Dewasa Di Wilayah Kerja Puskesmas Gunung Tua Kecamatan Panyabungan Kabupaten Mandailing Natal - Tanjung, Wiwi Wardani; ., Putri Handayani; ., Hotmaria Rambe (Jurnal Kesehatan Ilmiah Aufa Royhan, 2016)
Hypertension is a condition with blood pressure exceeds normal limits. If hypertension is not well controlled, it can result in damage to the blood vessels can even result in the risk of death. According to the Indonesia health profile of 2013 increased prevalence of hypertension is 9.55%. Data obtained from the District Health Center Old Mountain Panyabungan Mandailing Natal number of hypertensive patients increased from year 2013 to 2015. Hypertension ranks 3rd of 10 diseases PHC The Old Mountain. The objective of this study is to analyze the risk factors that influence the incidence of hypertension in adult women in Public Health Centre Gunung Tua Subdistrict Panyabungan Mandailing Natal 2016. This type of study was an analytic study with case control design. The population in this study were all adult women suffering from hypertension and who do not have hypertension amounted 96 respondents. The sample is a whole number of population used as a sample amounted 48 cases and 48 controls who had been in matching with age. Data obtained from health centers and through interviews using a questionnaire. Data analysis method was analyzed by univariate, bivariate used Chi-Square test at the level of 95% (P <0.05) and multivariate used multiple logistic regression. The results showed that variable hereditary obesity, dietary habits and stressful effect on the incidence of hypertension, while variable smoking and physical activity had no effect on the incidence of hypertension. It is recommended to health workers in health centers Gunung Tua to conduct health education to the public about how to prevent hypertension, for example by reducing the consumption of foods that trigger hypertension. Mandailing Natal Health Department is expected to create programs in an effort to overcome the problem of hypertension and in cooperation with other relevant agencies.